Pemanfaatan Limbah Sabut Kelapa melalui Penerapan Teknologi Produksi Cocopeat sebagai media tanam di Kota Ternate - Nurhikmah; Nurfadhilah Arif; Tuti Handayani Arifin (Altifani Journal: International Journal of Community Engagement, 2026)
Coconut plays an important role in the economic, cultural, and social life of Ternate City. Coconut is a leading commodity spread across several areas, namely in the Ternate Island sub-district (34.8 ha), Moti (205 ha), Batang Dua Island (365.6 ha), Hiri Island (58 ha), West Ternate (339.6 ha), South Ternate (12.6 ha), Central Ternate (36.7 ha), and North Ternate (26.6 ha). Of these sub-districts, West Ternate sub-district has a wider coconut distribution. The village in West Ternate sub-district that has coconut potential is Kulaba Village. The community uses coconut as its main product in the form of fresh coconut. Meanwhile, waste in the form of coconut fiber has not been utilized. This community service activity can be one solution to the problem of coconut fiber waste that has not been utilized so far and become a solution to the limited supply of planting media in Ternate City. The series of community service activities includes preparation, outreach, and training, covering the entire cocopeat production process, from sorting and chopping to washing and drying to packaging. The final stage is evaluation, which assesses the effectiveness and benefits of the activities.